Clinical and psychosocial benefits of 3D printing and virtual planning in complex facial reconstruction after oncological resection: a systematic review - Gwóźdź, Karolina; Zawadzka, Magdalena; Bystros, Aleksandra Natalia; Drozdowska, Marta; Marszałek, Dominika; Kurzątkowska, Klaudia; Borychowska, Emilia; Czudowska, Michalina; Ocimek, Aleksandra; Mierzejewska, Zofia Aneta (Quality in Sport, 2026)
Background. Head and neck cancers and their surgical treatment frequently lead to functional and aesthetic impairments that negatively affect patients’ quality of life and psychosocial functioning. The development of virtual surgical planning (VSP) and 3D printing has increased the precision of reconstructive procedures. Aim. To evaluate the clinical and psychosocial benefits of 3D printing and virtual surgical planning in facial reconstruction after oncological treatment. Materials and methods. A systematic review of the literature regarding computer-assisted surgery, CAD/CAM technologies, augmented reality, and 3D printing in craniofacial reconstruction following head and neck cancer resection was conducted. Results. The use of VSP and 3D printing improves the accuracy of resection and reconstruction, shortens operative time, and increases treatment predictability. Patient-specific implants and surgical guides enable better functional and aesthetic outcomes, improving mastication, swallowing, speech, and rehabilitation. These technologies also enhance physician–patient communication, increase treatment satisfaction, and support social reintegration. Conclusions. Virtual surgical planning and 3D printing significantly improve reconstructive treatment outcomes and quality of life in patients undergoing oncological surgery within the head and neck region.